Pergeseran Nilai Budaya Peziarah di Makam Raja-Raja Jera Lompo’e Kabupaten Soppeng - Hidayati, Fitri; Folanda, Gio (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2024)
This research aims to describe: (1) the shift of cultural values in pilgrims at the Tomb of the Kings of Jera Lompo'e, Soppeng Regency, South Sulawesi and (2) what factors caused the shift of cultural values in pilgrims at the tomb of rajaraja jera lompo'e in soppeng district. The type of research used is qualitative research with data collection techniques through observation, interviews and documentation. The results showed that: (1) there are several forms of cultural value shifts in pilgrims, namely: First, In the past, pilgrims were required to wear bodo clothes, but nowadays many pilgrims come in free clothes. Second, In the past, pilgrims were required to open their sandals, perform ablutions, and perform soro boko, but currently only a small number of pilgrims perform these rituals. And in the past, pilgrims came to the tomb with the main purpose of making a pilgrimage and praying for ancestors, but nowadays many visitors come only for sightseeing and taking pictures. (2) This shift in cultural values is caused by several factors, namely the times, lack of social awareness, and lack of encouragement from family and environment